Chronobiology as compensation: can biological rhythms compensate for sexual signals? - Westwood, Mary L.; Broder, E. Dale; Welsh, Gabrielle T.; Tinghitella, Robin M. (Frontiers in Ethology, 2025)
Conspicuous sexual signals come with costs and benefits. Such signals increase reproductive success but may also reduce survival or viability. It has recently been suggested that non-signal traits may alleviate some of those costs (termed “compensatory traits”). In this perspective piece, we argue that biological rhythms should be considered in the milieu of compensatory traits, as they can reduce the natural selection burden of signaling. This may be particularly true for the many sexual signals that are ephemeral (i.e., only periodically present like a courtship dance). Biological rhythms (e.g., circadian and circannual rhythms) are ubiquitous in nature and help organisms perform the right activity at the right time—this includes the timing of many sexual signals and reproductive traits. Timing itself may, in fact, reduce the costs of such sexual signals. Here, we review sexual signals that are governed by biological rhythms and discuss how signal modality and type (ornament, weapon, dominance trait) account for differences in how chronobiology may act as a compensatory trait. We then consider how biologists might examine the untested role of chronobiology as a compensatory trait and set forth compelling questions for future work.